Assessment of the impact of adding fly ash and coal bottom ash to an advanced cement-based composite matrix - Vieira,Mariana (2022)
Abstract To reduce environmental impact and hydration heat from high cement consumption in advanced cement-based composites, this study proposes the partial cement substitution by fly ash (FA) and coal bottom ash (CBA) in rates of 15% by mass (7.5% FA and 7.5% CBA) and 30% by mass (15% FA and 15% CBA). Matrixes were assessed for their physical and mechanical characteristics though the tests of compressive strength, capillary water absorption and ultrasonic pulse velocity, added to the analysis of images generated by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). Results indicated better performance of fly ash due to its particle size, shape and texture, especially for the rate of 15%. In terms of compressive strength, mixture RFA15 yielded the highest strength. The capillary water absorption results were linear and with low variations of about 1% and 5% between 28 and 56 days.